2017
DOI: 10.1093/mnras/stx343
|View full text |Cite
|
Sign up to set email alerts
|

The mass function of unprocessed dark matter haloes and merger tree branching rates

Abstract: A common approach in semi-analytic modeling of galaxy formation is to construct Monte Carlo realizations of merger histories of dark matter halos whose masses are sampled from a halo mass function. Both the mass function itself, and the merger rates used to construct merging histories are calibrated to N-body simulations. Typically, "backsplash" halos (those which were once subhalos within a larger halo, but which have since moved outside of the halo) are counted in both the halo mass function, and in the merg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 51 publications
0
43
0
Order By: Relevance
“…, which may be expected to be valid if the number of particles in each bin obeys Poisson statistics (Benson 2017a). We found that this leads to small but significant differences in the resulting distribution of concentration parameters.…”
Section: Uncertainties In N-body Concentration Estimatesmentioning
confidence: 68%
See 3 more Smart Citations
“…, which may be expected to be valid if the number of particles in each bin obeys Poisson statistics (Benson 2017a). We found that this leads to small but significant differences in the resulting distribution of concentration parameters.…”
Section: Uncertainties In N-body Concentration Estimatesmentioning
confidence: 68%
“…In the first, we generate spherically symmetric Einasto density profiles with a range of different concentrations, and sample from each profile using different numbers of particles via a Poisson process (Benson 2017a). These N-body representations are then fit using the procedure described above (without any application of the Power et al (2003) convergence criterion, which does not apply in this simple experiment).…”
Section: Uncertainties In N-body Concentration Estimatesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, halos that are temporarily linked together and subhalos that have been ejected from the host can both contribute to the progenitor mass function. The situation can become even worse if these objects fall back into the host and are counted multiple times (Benson 2017). In contrast, our approach of selecting branches located inside the final virial radius produces a progenitor population that can be unambiguiously compared against the final mass function inside the virial radius.…”
Section: Comparison With Fitting Functions and The Low Mass End Slopementioning
confidence: 99%